Role of CREB on heme oxygenase-1 induction in adrenal cells: Involvement of the PI3K pathway - Astort, Francisco (2016)
In addition to the well-known function of ACTH as the main regulator of adrenal steroidogenesis, we have previously demonstrated its effect on the transcriptional stimulation of HO-1 expression, a component of the cellular antioxidant defense system. In agreement, we hereby demonstrate that, in adrenocortical Y1 cells, HO-1 induction correlates with a significant prevention of the generation of reactive oxygen species induced by H2O2/Fe2+. ACTH/cAMP-dependent activation of redox-imbalanced related factors such as NRF2 or NFκB and the participation of MAPKs in this mechanism was, however, discarded based on results with specific inhibitors and reporter plasmids. We suggest the involvement of CREB in HO-1 induction by ACTH/cAMP, as transfection of cells with a dominant-negative isoform of CREB (DN-CREB-M1) decreased, while overexpression of CREB increased HO-1 protein levels. Sequence screening of the murine HO-1 promoter revealed CRE-like sites located at −146 and −37 of the transcription start site and ChIP studies indicated that this region recruits phosphorylated CREB (pCREB) upon cAMP stimulation in Y1 cells. In agreement, H89 (PKA inhibitor) or cotransfection with DN-CREB-M1 prevented the 8Br-cAMP-dependent increase in luciferase activity in cells transfected with pHO-1[−295/+74].LUC. ACTH and cAMP treatment induced the activation of the PI3K/Akt signaling pathway in a PKA-independent mechanism. Inhibition of this pathway prevented the cAMP-dependent increase in HO-1 protein levels and luciferase activity in cells transfected with pHO-1[−295/+74].LUC. Finally, here we show a crosstalk between the cAMP/PKA and PI3K pathways that affects the binding of p-CREB to its cognate element in the murine promoter of the Hmox1 gene.